Capture of Trumpeter Swans in British Columbia for H. M. Queen Elizabeth II - Lewis, Harrison F (Wildfowl, 1952)
About 900 Trumpeter Swans are believed to spend the summer in Canada. Most of them winter in British Columbia. The largest known wintering group, including about one hundred birds, is to be found at Lonesome Lake, a small body of water among forested mountains about two hundred and fifty miles north-west of Vancouver. Five cygnets were trapped and taken.